ANALISIS SIKAP KONSUMEN TERHADAP ATRIBUT SABUN MANDI (Studi Pada Sabun Mandi Merek Lux dan Giv Di Kota Malang) - Hence Izhar; Sumiati - -; Moeljadi P. - - (Wacana Journal of Social and Humanity Studies, 2010)
ABSTRACT Â  The study has as its rationale the fact that there are numerousÂ  brands of bath soap in the market. The changes of consumer behavior, which influenced by the economy crisis occurred in the Indonesia, has suppressed the producers to readjust their marketing programs. It is crucial for the firms to recognize the consumer attitudes on their marketing program. Moreover, consumer attitude is dominantly used in predicting the consumer behavior, in estimating the future demand of product, and in developing the appropriate marketing programs. The study aimed at understanding : (1). The consumer attitudes on the bath soaps (i.e, Lux and Giv brands) attributes, (2). The influence of the consumerâ€™s social environment toward the subjective norm in making the purchasing decisions on the Lux and Giv, (3). The differential of consumers attitudes on the Lux and Giv. Interview and questionnaire were used to collect data, by using the semantic differential scale method. Fishbein model and Wilcoxonâ€™s signed rank test were applied to the studyâ€™s results. The result of research indicate that : (1) There was a positive attitude of consumer on both the Lux and Giv. Attribute "Prestige" owning lowest positive score value for the brand of Lux and Giv, (2) Social environment from consumer influence consumer subjective norm of consumer in making the purchasing decisions of the Lux and Giv. â€œFamily Membersâ€ was the dominant variable of both the Lux and Giv, (3) Do not there are difference by significant attitude from consumer to product. Later, then different test to every attribute, do not there are difference by significant consumer attitude to product attribute. Based on the study results and empirical evidences supported by the statistical testing, it is showed that the two bath soap brands have dominated the consumerâ€™s mind. Nevertheless, in making their purchasing decisions, the consumers have the difference attitudes is assessing those two brands depends on their desires. Thus, it is suggested that the firms need to have variation and to differentiate their products to maintain the consumers loyalties, to develop some promotional strategies involving the sellers, to create the advertisements that strongly conspicuous the prominent attributes of the product, and to choose the ads media that can reach all consumer levels. Keywords : attitude consumer, attribute toilet soap